Trajnostno in večnamensko gospodarjenje z gozdovi ter proizvodnja visokokakovostnega lesa - Kotar, Marijan (Gozdarski vestnik, 2006)
The paper deals with definitions of sustainable forest management, multiple use of forests and nature-based forestry. In the last decades, sustainable forest management has evolved into sustainable forest ecosystem management. The prerequisite for sustainable forest ecosystem management and multiple use of forests is forestry as it is understood under the paradigm nature-based forestry. Multipurpose use of forests will be fulfilled optimally if forest production is aimed to production of high quality timber and if the tree composition of forest is suitable to site conditions. A large share of high quality timber can be achieved by well designed forest regeneration and foresttending. The possibility of increasing the quantity of timber productionin Slovenia is relatively small, while opportunities to increase theproduction of high quality timber are considerable. This can be achieved bysite appropriate tree composition and by better assortment structure in treestands.
Keywords: ekosistemi; gozdovi; gospodarjenje z gozdovi